2018
DOI: 10.1021/acsami.8b03477
|View full text |Cite
|
Sign up to set email alerts
|

Stable Dispersions of Covalently Tethered Polymer Improved Graphene Oxide Nanoconjugates as an Effective Vector for siRNA Delivery

Abstract: Conjugates of poly(amidoamine) (PAMAM) with modified graphene oxide (GO) are attractive nonviral vectors for gene-based cancer therapeutics. GO protects siRNA from enzymatic cleavage and showed reasonable transfection efficiency along with simultaneous benefits of low cost and large scale production. PAMAM is highly effective in siRNA delivery but suffers from high toxicity with poor in vivo efficacy. Co-reaction of GO and PAMAM led to aggregation and more importantly, have detrimental effect on stability of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 67 publications
2
64
0
Order By: Relevance
“…33 GO has been considered an ideal vector for gene delivery. 34,35 In this study, we demonstrated that GO-PEI was an effective nonviral carrier for miRNA delivery to suppress osteosarcoma cancer progression. GO bonded to PEI by electrostatic interactions and formed GO-PEI complexes with a positive charge (Figure 2).…”
Section: Discussionmentioning
confidence: 75%
“…33 GO has been considered an ideal vector for gene delivery. 34,35 In this study, we demonstrated that GO-PEI was an effective nonviral carrier for miRNA delivery to suppress osteosarcoma cancer progression. GO bonded to PEI by electrostatic interactions and formed GO-PEI complexes with a positive charge (Figure 2).…”
Section: Discussionmentioning
confidence: 75%
“…The stronger peak at approximately 399.8eV was attributed to the amine nitrogen (N–C). The amide nitrogen (O=C–N) occurred at approximately 401.9 eV as a result of the delocalization of the lone pair of electrons of O=C–N [38]. These analyses clearly indicated that PAMAM dendrimers were successfully grafted on the Pal surface.…”
Section: Resultsmentioning
confidence: 99%
“…Decrease in zeta potential values can be explained with the negative charge of pcDNA3-ING4 which was measured as -7.32 ± 5.35 mV. As a result, obtained net particle size and zeta potential values after the complexation procedure are sufficient for an efficient transfection [16].…”
Section: Dynamic Light Scattering (Dls) Measurementsmentioning
confidence: 91%